A Rare Complication in an Untreated Horizontal Root Fracture Case - Fatih Tulumbacı; Volkan Arıkan; Aylin Akbay Oba; Fethi Atıl (Selcuk Dental Journal)
Intra-alveolar root fractures in permanent teeth are rare following dental traumatic injuries. The diagnosis of root fractures depends on careful clinical and radiographic examination. The successful treatment of a root-fractured tooth involves repositioning and fixation. Although the outcome of a root fracture is generally favourable, complications such as pulpal necrosis, radicular resorption and pulpal canal obliteration can arise. A radicular cyst is an inflammatory cyst that develops as a result of untreated dental caries, with pulp necrosis and periapical infection following chemical, physical or bacterial injury. In this case report, the diagnosis and treatment of a rare case of a radicular cyst, which occurred as a result of pulp necrosis following horizontal root fracture, and an apical root fragment, which was displaced by the cystic lesion to the base of the nasal cavity, are presented.